SOME ASPECTS REGARDING 3D PRINTING OF DENTAL PROSTHESIS - Constanța RĂDULESCU; Liviu Marius CÎRȚÎNĂ; Tzvetelin GUEORGUIEV; Sînziana Caterina MUNTEANU; Alexandru PANAIT (Fiabilitate şi Durabilitate)
This paper presents how to import STL models, simulate the models before they are printed and print them. Depending on the choice of printing parameters, the quality of the parts surfaces is obtained. The material used to print the models is PLA, and they were printed on an Anycubic i3 Mega printer.The printed models have only a didactic and theoretical role.